Interactive introduction to first-order ordinary differential and its applications - Coelho, Celestino (2019)
Differential equations constitute a large and very important branch of modern mathematics. From the early days of the calculus this subject has been an area of great theoretical research and practical applications in several branches of science. Despite this importance, the largest part of the students reveals strong difficulties to understand the theory of differential equations and its applications. As a consequence of what was mentioned above we decided to create a new educational tool that accomplishes some of those goals, describing how this dynamic device can be used in the classroom when teaching the first approach of the first- order Ordinary Differential Equations (ODEs).